Dynamics of Trusting in Translation Project Management: Leaps of Faith and Balancing Acts. (August 2017) - Olohan, Maeve; Davitti, Elena
This paper examines the work of project managers in two UK-based translation companies. Drawing on participant observation, interviews, and artifacts from field sites, our analysis focuses on the ways in which trust is developed and maintained in the relationships that project managers build, on the one hand, with the clients who commission them to undertake translation projects, and, on the other, with freelance translators who perform the translation work. The project manager's ability both to confer and to instill trust is highlighted as key to the successful operation of the company. Conceptualizing trust as a dynamic process, we consider what this process of trusting entails in this context: positive expectations vis-à-vis the other parties; willingness to expose oneself to vulnerabilities; construction of bases for suspending doubts and uncertainties (leaps of faith). We observe the important role of communication and discursive strategies in building and maintaining trust and draw conclusions for translator education.